The prosecutor in transnational perspective - Luna, Erik; Wade, Marianne, Dr; Bojańczyk, Antoni (Oxford University Press, 2012)
"The American prosecutor plays a powerful role in the judicial system, wielding the authority to accept or decline a case, choose which crimes to allege, and decide the number of counts to charge. These choices, among others, are often made with little supervision or institutional oversight. This prosecutorial discretion has prompted scholars to look to the role of prosecutors in Europe for insight on how to reform the American system of justice. In The Prosecutor in Transnational Perspective, Erik Luna and Marianne Wade, through the works of their contributors coupled with their own analysis, demonstrate that valuable lessons can be learned from a transnational examination of prosecutorial authority. They examine both parallels and distinctions in the processes available to and decisions made by prosecutors in the United States and Europe. Ultimately, they demonstrate how the enhanced role of the prosecutor represents a crossroads for criminal justice with weighty legal and socio-economic consequences"--Provided by publisher